Virulence factors and antimicrobial resistance profiles of Campylobacter isolates recovered from consecutively reused broiler litter - Reed Woyda; Adelumola Oladeinde; Dinku Endale; Timothy Strickland; Jodie Plumblee Lawrence; Zaid Abdo (Microbiology Spectrum, 2023)
ABSTRACT Campylobacter infections are a leading cause of bacterial diarrhea in humans globally. Infections are due to consumption of contaminated food products and are highly associated with chicken meat, with chickens being an important reservoir for Campylobacter. Here, we characterized the genetic diversity of Campylobacter jejuni (C. jejuni) and Campylobacter coli (C. coli) detected in broiler chicken litter over three consecutive flocks and determined their antimicrobial resistance (ARM) and virulence factor (VF) profiles. Campylobacter was detected in 9.38% (27/288) of litter samples collected. Antimicrobial susceptibility testing and whole genome sequencing were performed on C. jejuni (n = 39) and C. coli (n = 5) isolates. Campylobacter virulence factors differed within and across broiler houses but were explained by the broiler flock cohort raised on litter, Campylobacter species and Campylobacter multilocus sequence type (MLST). Virulence factors involved in the ability to invade and colonize host tissues and evade host defenses were present in C. jejuni isolates (ST-464) from flock cohorts 1 and 2 but absent in C. jejuni isolates (ST-48) from flock cohort 3. C. jejuni isolates from house three harbored a significantly higher proportion of virulence genes with functions related to glycosylation and immune evasion than C. jejuni isolates from houses 1 and 2 (P < 0.01). All C. jejuni isolates were susceptible to all antibiotics tested while C. coli (n = 4) were resistant to tetracycline and harbored the tetracycline resistant ribosomal protection protein (TetO). Our results suggest that house environment and broiler management practices imposed selective pressures on virulence factors and antimicrobial resistance genes of Campylobacter. IMPORTANCE Campylobacter is a leading cause of foodborne illness in the United States due to consumption of contaminated or mishandled food products, often associated with chicken meat. Campylobacter is common in the microbiota of avian and mammalian gut; however, acquisition of antimicrobial resistance genes (ARGs) and virulence factors (VFs) may result in strains that pose significant threat to public health. Although there are studies investigating the genetic diversity of Campylobacter strains isolated from post-harvest chicken samples, there are limited data on the genome characteristics of isolates recovered from preharvest broiler production. Here, we show that Campylobacter jejuni and Campylobacter coli differ in their carriage of antimicrobial resistance and virulence factors may also differ in their ability to persist in litter during consecutive grow-out of broiler flocks. We found that presence/absence of virulence factors needed for evasion of host defense mechanisms and gut colonization played an integral role in differentiating Campylobacter strains.